Study habits of physical therapy students in remote teaching (Research, Society and Development, 2022)
In 2020 there was the massive transfer of students who had been following the college in person for remote education, as a solution to the COVID-19 pandemic. Thus, it was necessary to reformulate the way of teaching, where teachers had to be able to use the appropriate digital technologies to provide remote teaching to students, who in turn also had to adapt and seek study and learning strategies. Thus, this study aimed to analyze the study habits of physiotherapy students in remote teaching. This is a cross-sectional, descriptive, quantitative approach, conducted with physical therapy students from a private higher education institution. Data collection occurred through a questionnaire containing objective questions, using the Google Forms platform. The study included 262 students, 76.72% of them female, with a mean age of 20.16 years, belonging to the last years of the course (54.58%). The largest proportion reported never having failed subjects (61.83%), claiming to study remotely between one and three hours a day (37.79%) and presented inadequate study habits in all categories investigated. When analyzing self-perception of income in this type of teaching, inadequate habit is predominant in all perceptions of academic performance. Knowledge of the student profile, together with their academic perceptions and study habits, can confer necessary adaptations to the continuity of the teaching-learning process in remote teaching.